Supporting research readiness in social enterprise health services - Nat M. J. Wright; Philippa Hearty; Linda Harris; Andrew Burnell; Sue Pender; Chris Oxnard; George Charlesworth (BMC, 2017)
Abstract Health-based social enterprises are spun out of the NHS, yet continue to provide NHS-funded services. With the spin-out, however, formal processes for research governance were lost. Patients have a right to take part in research, regardless of where they access healthcare. This paper discusses the barriers to social enterprises undertaking applied health research and makes recommendations to address the need for equivalence of governance processes with NHS trusts.